Figure 1 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 1. (A) Amphileptus sp., (B) Pleuronema coronatum and (C) Philasterides cf. armatalis after protargol impregnation. (A) Right side view of infraciliature, arrows mark the suture formed by some shortened kineties, arrowheads indicate the extrusomes; (B) ventral-left view, to show the general appearance of infraciliature and nuclear apparatus (arrows mark the micronuclei); (C) left side view, arrowhead marks the apical plate; arrow indicates the anterior end of paroral membrane, double-arrowheads mark the scutica. Ma, macronucleus; M13, membranelle 1, 3. Scale bars: 70 Mm (A); 30 Mm (B); 15 Mm (C). : Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 937, DOI: 10.1080/00222930400001509, http://zenodo.org/record/4657793